Nepal’s women leaders champion inclusive development - Khadka, Manohara; KC, Sumitra (Dialogue Earth, 2024)
Since Nepal’s shift to a federal structure in 2015, a new generation of women leaders has emerged, dedicated to water management, sustainability and equitable development. However, entrenched systems and outdated norms continue to hinder their progress.